IMPROVING STUDENTS’ READING COMPREHENSION THROUGH REHEARSAL STRATEGY - Satang, Satang (REVIEW OF MULTIDISCIPLINARY EDUCATION, CULTURE AND PEDAGOGY, 2024)
Reading serves as the foundation for instruction in all aspects of language learning, including using textbooks for language courses, writing, revising, developing vocabulary, acquiring grammar, and utilizing computer-assisted language learning programs. The objectives of this study were to examine: (1) Whether the implementation of the Rehearsal Strategy enhances the reading comprehension skills of second-semester students at Muhammadiyah University of Makassar; (2) The students' perception regarding the utilization of the Rehearsal Strategy in improving reading comprehension. The study was conducted with second-semester students from the English Department at Muhammadiyah University of Makassar. A quasi-experimental design was employed, consisting of a pre-test, eight treatment sessions, and a post-test. Data were collected using a reading test and a questionnaire, and were analyzed using statistical methods such as independent sample t-test and frequency analysis of the questionnaire. The findings of the study revealed that the p-value of the independent t-test for the post-test scores was less than 0.05, indicating a significant difference in reading comprehension between students taught with the rehearsal strategy and those without it. The analysis of the questionnaire demonstrated that the students held a highly positive perception towards the implementation of the Rehearsal Strategy.